RELASI KEKUASAAN DALAM PEMBELAJARAN KIMIA PADA SMA RINTISAN SEKOLAH BERTARAF INTERNASIONAL DI BALI - Wiratma, I Gusti Lanag (Universitas Pendidikan Ganesha, 2015)
Abstract: Power Relation in Chemistry Instruction at Pilot Project of International Senior High School in Bali. This study aimed at explaining the relation between the power and meanings behind the phenomenon occurred in the chemistry instruction in pilot project of international senior high school (RSBI) in Bali. The study employed a qualitative method in particular phenomenological approach. The data were collected by using observation, interview, and document study. The instruments used were observation sheet, interview guideline, and check list. Subsequently, the collected data were analysed in a descriptive interpretative approach. The results show that the chemistry instruction has not yet conducted optimally due to lack of laboratory practices. This is resulted from the presence of hegemonic structure among the authority from the top to lower level and ultimately exert the power to students. As the consequence, the students do not obtain maximum learning experience as required by the curriculum and most likely they experience the unbalance of intelligence development as it was prioritized on cognitive rather than affective and psychomotor. This situation was worsened by the political imaging set up by the authorities to maintain their status quo that leads to co-modification culture in education. Keywords: co-modification, education, laboratory, RSBI Abstrak: Relasi Kekuasaan dalam Pembelajaran Kimia pada SMA Rintisan Bertaraf Internasio-nal di Bali. Penelitian ini bertujuan untuk menjelaskan relasi kekuasaan dan makna di balik fenomena yang terjadi pada pembelajaran kimia SMA Rintisan Sekolah Bertaraf Internasional (RSBI) di Provinsi Bali. Metode penelitian yang digunakan adalah metode kualitatif, dengan pendekatan fenomenologis. Cara pengambilan data dilakukan dengan observasi, wawancara, dan studi dokumen. Instrumen yang di-gunakan adalah pedoman observasi, pedoman wawancara, dan daftar chek (check list). Teknik analisis data yang digunakan adalah analisis diskriptif interpretatif. Hasil penelitian menunjukkan bahwa pem-belajaran kimia belum dilakukan secara optimal karena sangat minim melakukan pembelajaran praktik di laboratorium. Hal ini disebabkan karena adanya hegemoni terstruktur yakni dari penguasa yang lebih tinggi ke penguasa yang lebih rendah, sampai pada siswa. Siswa tidak memeroleh pengalaman belajar yang maksimal seperti yang tertera di dalam kurikulum. Perkembangan kecerdasan siswa tidak se-imbang, lebih mengutamakan ranah kognitif dari pada afektif dan psikomotor. Kondisi ini tercipta kare-na adanya kepentingan politik pencitraan untuk mempertahankan status quo yang cenderung mengarah pada budaya komodifikasi pendidikan. Kata-kata Kunci: komodifikasi, laboratorium, pendidikan, RSBI